IMPLEMENTATION OF QUALITY FAMILY VILLAGES IN BERINGIN IN PESISIR VILLAGE, LIMAPULUH DISTRICT, PEKANBARU CITY - Atika Suryani; Devi Deswimar (Yayasan Wayan Marwan Pulungan, 2026)
The Quality Family Village (Kampung KB) is a government strategy to develop quality families through the integration of population, family planning, family development, and community empowerment programs. This study aims to analyze the implementation of the Beringin Quality Family Village in Pesisir Village, Limapuluh District, Pekanbaru City. A descriptive qualitative approach was employed. Informants were selected using purposive sampling and included the Head of the Kampung KB Executive, Family Planning Field Counselors (PLKB), cadres, midwives, the Pesisir Village Head, and community members as program beneficiaries. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, including data condensation, data display, and conclusion drawing. The findings show that the implementation of the Beringin Quality Family Village has generally been carried out in accordance with program objectives. Based on the indicators of program suitability with the target group, suitability with the implementing organization, and compatibility between the target group and implementing organization, the program addresses community needs through various activity groups, although some activities have not been consistently implemented. The implementing organization has received cross-sectoral support and conducted coordination and monitoring, despite limitations in reporting and data updating. Communication between implementers and the community has been effective; however, community participation in several activities remains limited. Strengthening activity sustainability, increasing community participation, and improving monitoring and evaluation systems are essential to enhance the effectiveness of the program in developing quality families.